Dysregulation in Plasma ω3 Fatty Acids Concentration and Serum Zinc in Heavy Alcohol-Drinking HCV Patients - Vatsalya Vatsalya; Ruchita Agrawal; Jane Frimodig; Shweta Srivastava; Melanie L. Schwandt (Advances in Virology)
Alcohol use disorder (AUD) patients comorbid with hepatitis C virus (HCV) infection (HCV + AUD) could have progressively severe clinical sequels of liver injury and inflammation. Serum zinc and several polyunsaturated fatty acids (PUFAs) get dysregulated in AUD as well as HCV. However, the extent of dysregulation of PUFAs and zinc deficiency and their interaction in HCV + AUD as a comorbid pathology has not been studied. We examined the role of dysregulation of FAs and low zinc in HCV + AUD patients. 138 male and female participants aged 21–67 years were grouped as HCV-only (Gr. 1; n = 13), HCV + AUD (Gr. 2; n = 25), AUD without liver injury (Gr. 3; n = 37), AUD with liver injury (Gr. 4; n = 51), and healthy volunteers (Gr. 5 or HV; n = 12). Drinking history, individual demographic measures, fasting fatty acids, liver function, and zinc were measured and analyzed. HCV + AUD patients showed the highest ALT level compared to the rest of the groups. Serum zinc concentrations were the lowest, and the proinflammatory shift was the highest (characterized by ω6 : ω3 ratio) in the HCV + AUD patients. Total ω3, eicosapentaenoic acid (EPA), and docosapentaenoic acid (DPA5,3) were the lowest in HCV + AUD patients. Total ω3, α-linoleic acid (α-LA) along with covariable number of drinking days past 90 days (NDD90), eicosapentaenoic acid (EPA), and docosapentaenoic acid (DPA5,3) independently showed significant association with low zinc in the HCV + AUD patients. Heavy drinking pattern showed that NDD90 has a significant mediating role in the representation of the relationship between candidate ω3 PUFAs and zinc uniquely in the HCV + AUD patients. Low serum zinc showed a distinctively stronger association with total and candidate ω3s in the HCV + AUD patients compared to the patients with HCV or AUD alone, supporting dual mechanism involved in the exacerbation of the proinflammatory response in this comorbid cohort. This trial is registered with NCT#00001673.